Subtractive renormalization of one-pion-exchange and contact interactions - Timóteo, V. S.; Frederico, T.; Delfino, A.; Tomio, L. [UNESP] (Sociedade Brasileira de Física, 2005)
A recursive subtractive renormalization of the scattering equation is applied to the nucleon-nucleon ¹S0 channel with one-pion-exchange plus derivative contact interactions. This method can be easily extended to any derivative order of the singular interaction. Although we limit this work to the singlet partial wave, the method can be used as well in higher waves and coupled channels. The ¹S0 renormalization parameters are fitted to the data.